Influence Factors of Vibration Response on Supporting-Thrusting System of Tunnel Boring Machine. (29th July 2020) - Mei, Yongbing; Xia, Yimin; Lin, Laikuang; Cheng, Yongliang; Qian, Cong
Abstract : A supporting-thrusting system is the main load-bearing component of a tunnel boring machine (TBM) and the centralization of vibration response under TBM working. This study combines the structure and working principle of the supporting-thrusting system. Based on the vibration theory and test results at a construction site, the main influence factors of the vibration response of the supporting-thrusting system are the main beam structure, the characteristic parameters of advance cylinder, and the support pressure to surrounding rock. Under the different influence factors, the vibration response of the supporting-thrusting system is calculated and analyzed via computer simulation. The results indicate that, under the equivalent input-load on the TBM and increase in the length of the front main beam, the vibration acceleration at the front area of the TBM increases. The change rate of vertical vibration will be maximum, while the vibration acceleration at the rear area of TBM decreases. When the structure size of the thrusting cylinder increases, the vibration acceleration on the main beam decreases and those of the gripper shoe and saddle frame increase. However, the response to the axis vibration is the most sensitive. As the horizontal support pressure to the surrounding rock increases, the vibration acceleration on supporting-thrusting system decreases. When the level of support pressure exceeds 1.6 e 4 kN, the vibration acceleration changes gradually. These results provide a reference for designing and operating TBM parameters.